Pengaruh Abu Dan Proporsi Pasir-Kompos Di Dalam Media Pada Pertumbuhan Tanaman Sorgum (Sorghum bicolor L.) - Andrian isro rahmadi; Tundjung Tripeni Handayan; Martha L Lande (Politeknik Negeri Lampung., 2016)
The aim of this experiment was to determine the effect of the addition of ash and sand-compost proportion in the media on the growth of sorghum (Sorghum bicolor L.). Theexperiment was conducted on December 2015 to January 2016 in the Botanical Laboratory,Biology Department, Faculty of Mathematic and Natural Science, Lampung University, andwas conducted in a complete randomized design by using two treatments. The first treatmentwas the addition of ash in two equivalents (with and without ash), the second treatment wasthe addition of sand-compost proportion in four equivalents (2 kg of sand, 1¾ kg of sand +¼ kg of compost, 1½ kg of sand + ½ kg of compost, 1¼ kg of sand + ¾ kg of compost). Theobserved variables of the growth were the number of the roots, the crown’s length, the wetweight, and the dry weight. The number of the roots was determined by observing thenumber of the roots present at the base of the stalk of each plants. The length of the crown(cm) was determined by measuring it from the stalk’s base to the edge of the longest leaf.The wet weight (g) was determined by measuring the whole part of the plant using ananalytical balance. The dry weight (g) was measured after the plants were stored in an ovenfor three hours in the temperature of 70o-80oC. The result showed that the best growth wasobtained from the media with the sand equivalent of 1¼ kg of sand added with ¾ kg ofcompost without ash.Key words: Ash, compost, growth of sorghum (Sorghum bicolor L.), sand